Morphological And Histological Structure of Female Reproductive System of Streptopelia Senegalensis - Abdul Wahab, Sura Abdul Munaff (The Indian Journal of Animal Reproduction, 2026)
This study presents a descriptive morphological and histological examination of the ovary and oviduct of Streptopelia sen egalensis. The topographical analysis provided that the ovary was like a bunch of grapes whose mean weight was 0.37 ± 1 gm and the mean follicle size was 3.55 ± 1 mm. The oviduct, a flexible folded muscular tube, weighed 0.45 ± 0.1 gm with a total length from the tip to the utero-vaginal junction of 77.78 ± 3.6 mm. The ovary had two histological segments: the cortex and the medulla. The wall of the oviduct comprised four coats: tunica mucosa, tunica submucosa, tunica mus cularis, and tunica serosa. The mucosa of the oviduct was folded, composed of ciliated pseudostratified columnar epi thelium with secondary and tertiary folds visible throughout the sections, and it was lined with ciliated pseudostratified columnar epithelium. These findings contribute to a deeper understanding of the reproductive anatomy and functional adaptations of S. senegalensis.